Mechanism of low-salt surimi gelation induced by microwave heating combined with l-arginine and transglutaminase: On the basis of molecular docking between l-arginine and myosin heavy chain. (15th October 2022) - Shi, Tong; Wang, Xin; Li, Mengzhe; Xiong, Zhiyu; McClements, David Julian; Bao, Yulong; Song, Teng; Li, Jianrong; Yuan, Li; Jin, Wengang; Gao, Ruichang
Highlights: Arg combined with TGase improved the gel properties of low-salt surimi induced by MW. A compact network of low-salt surimi gel was obtained if Arg was added before TGase. Arg increased proportion of immobilized water and decreased proportion of free water. Arg induced a shift of α-helix bands and increase in definition of β-sheet bands. The binding sites between Arg and myosin were revealed via molecular docking technique. Abstract: The reduction of the salt content of foods is of interest for health reasons. The present study showed that low-salt surimi gels could be produced using a combination of l -arginine (Arg) and transglutaminase (TGase) under microwave (MW) irradiation. The low-salt surimi gels produced by MW had similar physicochemical properties as regular-salt surimi gels produced by conventional two-stage water bath heating. Compared to low-salt surimi gels containing TGase alone, Arg increased the water holding capacity and gel strength ( P  < 0.05) and promoted the formation of a more homogeneous and compact three-dimensional gel network. As a result, there was a significant increase in the proportion of immobilized water and decrease in the proportion of free water ( P  < 0.05). The nature of the binding sites between Arg and myosin heavy chain was predicted using the molecular docking simulations analysis. These results may be useful for the development of low-salt surimi products.